A Taxonomy of Supports and Barriers to Family-Centered Adult Critical Care: A Qualitative Descriptive Study. (August 2021) - Thirsk, Lorraine Marie; Vandall-Walker, Virginia; Rasiah, Jananee; Keyko, Kacey
Family-centered care (FCC) improves the quality and safety of health care provision, reduces cost, and improves patient, family, and provider satisfaction. Despite several decades of advocacy, research, and evidence, there are still challenges in uptake and adoption of FCC practices in adult critical care. The objective of this study was to understand the supports and barriers to family-centered adult critical care (FcACC). A qualitative descriptive design was used to develop a taxonomy. Interviews and focus groups were conducted with 21 participants in Alberta, Canada, from 2013 to 2014. Analysis revealed two main domains of supports and barriers to FcACC: PEOPLE and STRUCTURES . These domains were further classified into concepts and subconcepts that captured all the reported data. Many factors at individual, group, and organizational levels influenced the enactment of FcACC. These included health care provider beliefs, influence of primary versus secondary tasks, perceptions of family work, nurses' emotional labor, and organizational culture.